Advanced oxidation processes: Performance, advantages, and scale-up of emerging technologies. (15th August 2022) - Priyadarshini, Monali; Das, Indrasis; Ghangrekar, Makarand M.; Blaney, Lee
Abstract: Advanced oxidation processes (AOPs) are promising technologies for partial or complete mineralization of contaminants of emerging concern by highly reactive hydroxyl, hydroperoxyl, superoxide, and sulphate radicals. Detailed investigations and reviews have been reported for conventional AOP systems that have been installed in full-scale wastewater treatment plants. However, recent efforts have focused on the peroxymonosulphate, persulphate, catalytic ozonation, ultrasonication and hydrodynamic cavitation, gamma radiation, electrochemical oxidation, modified Fenton, and plasma-assisted AOPs. This critical review presents the detailed mechanisms of emerging AOP technologies, their performance for treatment of contaminants of emerging concern, the relative advantages and disadvantages of each technology, and the remaining challenges to scale-up and implementation. Among the evaluated technologies, the modified electrochemical oxidation, gamma radiation, and plasma-assisted systems demonstrated the greatest potential for successful and sustainable implementation in wastewater treatment due to their environmental safety, compatibility, and efficient transformation of contaminants of emerging concern by a variety of reactive species. The other emerging AOP systems were also promising, but additional scale-up trials and a deeper understanding of their reaction kinetics in complex wastewater matrices are necessary to determine the technical and economic feasibility of full-scale processes. Highlights: Recent updates in the field of advanced oxidation processes are summarized. Advantages, and disadvantages of emerging advanced oxidations are elucidated. Real-scale commercialization status of emerging advanced oxidations are discussed. Bottlenecks and prospects related to advanced oxidations are discussed.